Stainless Steel Metal Corrosion Induction by Water Contained Sulphur in Geothermal Well - AHMED, ELLYSHA; Zaidi Embong,; Khawarizmi Jafery, (Enhanced Knowledge in Sciences and Technology, 2024)
The study investigates the impact of sulfur on the corrosion of stainless-steel samples immersed in geothermal hot spring water. Stainless steel, known for its corrosion resistance due to forming a protective oxide layer, faces challenges in geothermal environments, exacerbated by sulfur compounds. Advanced techniques such as SEM-EDX, FTIR, and Raman Spectroscopy were employed for detailed analysis. After 7 days of immersion, SEM-EDX revealed initial corrosion with cracks and grains, progressing to severe damage after 14 days. FTIR detected various spectra that highlight unique spectral features corresponding to abundant functional groups in the FTIR spectrum of the steel sample, including amine group (N-H), thiocyanate (S-C=N), sulfoxide (S=O), phenol group (O-H) while Raman Spectroscopy identified corrosion products on the steel surface and identified that several oxides were found in the analysis such as α-FeOOH(goethite), γ-FeOOH (lepidocrocite) and Fe3O4 (magnetite). The study provides crucial insights into the corrosion processes at both micro and molecular levels, addressing the durability issues of stainless steel in geothermal power generation.